Scientific principles of classification of regime-forming objects (on the example of water objects) - Dorosh, Y.; Dorosh, O.; Kupriianchyk, I.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2023)
The study of scientific works, normative legal acts related to issues of classification of regime-forming objects, restrictions on the use of land and land plots made it possible to identify problems related to regime-forming water objects that need to be solved. In accordance with this, the conceptual apparatus related to regime-forming water objects was considered, their list was standardized taking into account the current legal acts and the need for their classification was substantiated. As a result, a classification of regime-forming water objects is proposed, which will allow to further form the limits of restrictions along and around these objects and to develop a classification of restrictions on the use of land and land plots. According to the proposal of the author’s team, this classification can become an analogue for the classification of other objects, such as: an object of main pipelines, an energy object, an object of cultural heritage, military objects. It is justified that the creation of a single structure of classification is not possible, since each of these objects, when classified from general to specific, will have different levels of classification and require the development of individual approaches to their classification. Keywords: regime-forming objects, water objects, restrictions on the use of land plots, classification.